Potential Mechanisms Connecting Purine Metabolism and Cancer Therapy - Yin, Jie; Ren, Wenkai; Huang, Xingguo; Deng, Jinping; Li, Tiejun; Yin, Yulong (Frontiers in Immunology, 2018)
Unrestricted cell proliferation is a hallmark of cancer. Purines are basic components of nucleotides in cell proliferation, thus impaired purine metabolism is associated with the progression of cancer. The de novo biosynthesis of purine depends on six enzymes to catalyze the conversion of phosphoribosylpyrophosphate to inosine 5'-monophosphate. These enzymes cluster around mitochondria and microtubules to form purinosome, which is a multi-enzyme complex involved in de novo purine biosynthesis and purine nucleotides requirement. In this review, we highlighted the purine metabolism and purinosome biology with emphasis on the therapeutic potential of manipulating of purine metabolism or purinosome in cancers. We also reviewed current advances in our understanding of mammalian target of rapamycin (mTOR) for regulating purinosome formation or purine metabolism in cancers, and discussed the future prospects for targeting purinosome to treat cancers.